2008
DOI: 10.1118/1.3003063
|View full text |Cite
|
Sign up to set email alerts
|

Analytical optimization of digital subtraction mammography with contrast medium using a commercial unit

Abstract: Contrast-medium-enhanced digital mammography (CEDM) is an image subtraction technique which might help unmasking lesions embedded in very dense breasts. Previous works have stated the feasibility of CEDM and the imperative need of radiological optimization. This work presents an extension of a former analytical formalism to predict contrast-to-noise ratio (CNR) in subtracted mammograms. The goal is to optimize radiological parameters available in a clinical mammographic unit (x-ray tube anode/filter combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…5 Our group has proposed a combination of both schemes called DE temporal (DET) 6 which offers advantages in the contrast-to-noise ratio of the resulting image; this proposal has been validated by data from a homogeneous phantom. 7 Under optimum performance of the technique, both subtraction modalities, SET and DET-if applied to the same set of images containing a given amount of iodine-should deliver equivalent results in terms of contrast, which under appropriate calibration can be translated into CM mass thickness.…”
Section: Introductionmentioning
confidence: 99%
“…5 Our group has proposed a combination of both schemes called DE temporal (DET) 6 which offers advantages in the contrast-to-noise ratio of the resulting image; this proposal has been validated by data from a homogeneous phantom. 7 Under optimum performance of the technique, both subtraction modalities, SET and DET-if applied to the same set of images containing a given amount of iodine-should deliver equivalent results in terms of contrast, which under appropriate calibration can be translated into CM mass thickness.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the impact of α on iodine detectability, contrast-to-noise ratio (CNR) was calculated in DE images with different α. The standard expression for CNR is ( 2 ) where V ρ , V 0 , σ ρ , σ 0 correspond to the mean HU and the standard deviation of resin with ρ and 0 mg/ml iodine concentration, respectively. A CNR expression explicitly dependent on α, and derived from the operational definition of the DE subtraction (Eq.…”
Section: Dual-energy Imagingmentioning
confidence: 99%
“…2 Usually in DE studies, an iodinated contrast medium (CM) is used to increase the contrast between uptake organs and surrounding tissue. The DE technique has been used to distinguish CM from bone, calcium and gold-based nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we address the application of CEDM with a GE Senographe unit ͑GE Healthcare, Milwaukee, WI͒ because of its technical features ͑dual-track anode and wide voltage range͒ as well as the commercial prevalence in the U.S. and worldwide. 15 A recent work based on the analytical optimization of temporal and dual-energy applications of the CEDM technique with this commercial unit 16 has suggested that, although optimum spectral combinations were those including high-voltage strongly hardened Rh/Rh spectra, the use of Mo mammographic spectra for imaging the iodinated structure might provides a large advantage in contrast ͑of about 40%͒ over the optimized option. Due to this and the simplicity of use, low-energy spectra ͑below the iodine K edge͒ might represent an interesting alternative to higherenergy, hardened x-ray beams.…”
Section: Introductionmentioning
confidence: 99%